One Hundred Years of Inertia: An Exposé of the Concept of the Psychosocial Work Environment in Swedish Policy and Research - Abrahamsson, Lena; Johansson, Jan (Nordic Journal of Working Life Studies, 2013)
The purpose of this article is to describe a broader concept of the psychosocial work environment, a concept that not only is limited to the individual and her immediate environment but also takes into account a broader context that includes production technology as well as work organization and learning. Based on examples from Sweden, we discuss concepts and approaches to psychosocial work environment and how these have changed over time (e.g., how knowledge about the psychosocial work environment is used to understand and discuss health, management, and development—for individuals, groups, and organizations). The knowledge presented is not new; it has been around a long time. The title of the article—One Hundred Years of Inertia—shows some impatience on the part of its authors given that the pace of change in the work environment has not always been great.